Fibrous and flexible supercapacitors comprising hierarchical nanostructures with carbon spheres and graphene oxide nanosheets. Issue 24 (28th June 2015) - Zhang, Xiong; Lai, Yuekun; Ge, Mingzheng; Zheng, Yaxin; Zhang, Ke-Qin; Lin, Zhiqun
<x xml:space="preserve">Abstract</x> A fibrous and flexible graphene nano-sheet and carbon nano-sphere composite supercapacitor is developed by a novel electrochemical approach and its stable performance with a highly enhanced capacitance is demonstrated.